2017
DOI: 10.1016/j.jtusci.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiation improves biodiesel yields from waste cooking oil in the presence of modified coal fly ash

Abstract: This paper studied the effects of using modified coal fly ash as a catalyst to convert waste cooking oil (WCO) into biodiesel under microwave-strengthened action. Coal fly ash was modified with sodium sulphate and sodium hydroxide, and the obtained catalyst was characterized using FT-IR and X-ray diffraction (XRD). The experimental results showed that the modified coal fly ash catalyst improved biodiesel yields under the microwave-assisted system, and the maximum biodiesel yield from waste cooking oil reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 35 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…The results show that the produced biodiesel mainly contains oleic acid methyl ester (31.52%), palmitoleic acid methyl ester (29.43%), stearic acid methyl ester (26.95%) and other components as shown in Figure 9. The results obtained were in line with previous studies [48,49], which reported that biodiesel from WFO was mainly composed of stearic-, oleic-, palmitic-and palmitoleic acids. The results also revealed that the proportion of monounsaturated fatty acids found in biodiesel was higher than the proportion of saturated fatty acids.…”
Section: Biodiesel Compositionsupporting
confidence: 92%
“…The results show that the produced biodiesel mainly contains oleic acid methyl ester (31.52%), palmitoleic acid methyl ester (29.43%), stearic acid methyl ester (26.95%) and other components as shown in Figure 9. The results obtained were in line with previous studies [48,49], which reported that biodiesel from WFO was mainly composed of stearic-, oleic-, palmitic-and palmitoleic acids. The results also revealed that the proportion of monounsaturated fatty acids found in biodiesel was higher than the proportion of saturated fatty acids.…”
Section: Biodiesel Compositionsupporting
confidence: 92%
“…This proved the interdependency between catalyst loading and methanol to oil molar ratio, as the optimal levels of both factors are required to produce 100% FAME yield. The poor FAME yield at the joint permutation of low methanol to oil molar ratio and low catalyst loading was caused by insufficient catalyst concentration in the reaction mixture to complete the transesterification reaction [42]. Beyond a catalyst loading of 1.0 wt.%, it is postulated that transesterification would be adversely affected by undesired emulsification and saponification, complicating product separation and diminishing the FAME yield, respectively [43].…”
Section: Combined Effects Of Reaction Temperature and Catalyst Loadingmentioning
confidence: 99%
“…Thus, the use of this industrial residue as a biodiesel catalyst not only reduces costs but also controls pollution (Ram and Masto, 2014). Studies by Xiang et al (2016Xiang et al ( , 2017 disclosed that hydrothermal treatment of coal fly ash can yield around 95% biodiesel by microwave radiation, and more than 95% by ultrasonic irradiation using waste cooking oil as a biodiesel feedstock. Furthermore, studies by Manique et al (2017) disclosed that hydrothermal synthesis of coal fly ash zeolite can yield over 95% biodiesel.…”
Section: Coal Fly Ashmentioning
confidence: 99%